The Content of Lead Metals in Water and Green Shells (Perna viridis) in the Waters of Tanjung Emas Semarang - Rizkita Dimar Agnevia; Ni Luh Watiniasih; Alfi Herawati Waskita Sari (Program Magister Ilmu Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
Tanjung Emas waters are a coastal area in Semarang City which is a productive area and has potential resources for the country's development in the economic field. The existence of industrial activities and ports in the waters of Tanjung Emas Semarang is suspected to be a contributor to the influx of heavy metals such as Lead (Pb) into the waters. Changes in the polluted water environment will affect the survival of conch animals because these animals have limited mobility and are easily affected by the presence of pollutants, both physical and organic pollutants. The waters of the Port of Tanjung Emas Semarang functioned as a place for fish farming and cultivation of clam. One of them is green shells (Perna viridis). Shellfish belong to the type of filter animal (filter feeder). Water samples and extracted green shells (Perna viridis) were measured for lead content (Pb) using the AAS (Atomic Absorption Spectrophotometer) tool which refers to SNI 6989.4.2009 for water and SNI 01.2896.1998 for green shells (Perna viridis). The results of this study found that the concentration of heavy metals in shells was higher than in water. The measurement results of heavy metals lead (Pb) in water ranged from 0.008 to 0.010 Mg / L while the values ​​in green shells (Perna viridis) ranged from 0.274 to 0.320 Mg / Kg Then for water quality parameters the pH value ranges from 7 to 7.7 while the temperature value is 28.6 - 29.8o C and the value of dissolved oxygen (DO) is 5 - 5.2 ppm. Keywords: Heavy Metal, Pb, Water, Green Shells